Preparation and Use of (γ,γ-Dioxyallyl)boronates - Nishino, Soshi; Nishii, Yuji; Hirano, Koji (Synlett, 2023)
A copper-catalyzed stereoselective 1,4-acylboration of α,β-unsaturated esters with B2pin2 and pivalic anhydride has been developed to afford the corresponding (E)-allylboronates with two distinct oxygenated functionalities at the γ positions, which are difficult to prepare by other means. The chemoselective post functionalizations of Bpin and pivalate moieties in the product are also demonstrated.
Keywords: allylboronate; borylation; conjugate addition; copper; stereoselectivity